LA TRANSFORMACIÓN DE LAS MENTALIDADES CRISTIANAS Y LA EVOLUCIÓN DE LAS ORGANIZACIONES ECLESIÁSTICAS ESTADOUNIDENSES (1840-1945) - Abreu Colombri, José Antonio (Debates do NER, 2023)
Like the Christian belief system, the mindsets of the many established Christian communities in the United States have changed over time. The article tries to establish a period of great transformation at a social and cultural level, which goes from the great transformation of the later period until the end of the Second World War. In a generalized way, almost all the ecclesiastical organizations linked to the branch of Reformed Protestantism expanded geographically and demographically, this trend also led to an intense propagation of the moral principles and biblical interpretations of this Protestant confessional bloc. On the other hand, the ecclesiastical organizations linked to the main line of Protestantism lost an important part of their social mass, while conserving their social influence and their capacity for cultural leadership. The complexity of the institutions and diversity of Christian thought, from different conjunctural approaches, are studied in all the thematic sections of this study.